21 LESSONS FOR THE 21TH CENTURY HUMAN SEARCH FOR THE MEANING OF EXISTENCE - V. L. Sinta Herindrasti (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2018)
After Sapiens A Brief History of humankind (2011) and Future Homo Deus of the human race (2015), Prof. Harari published the third book part of his trilogy, Lessons for the 21st Century in 2018